2016
DOI: 10.1136/heartjnl-2015-309026
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term cardiovascular risk, metabolic syndrome and HIV in Tanzania

Abstract: Objective To compare short and long term cardiovascular disease (CVD) risk scores and prevalence of metabolic syndrome in HIV-infected adults receiving and not receiving antiretroviral therapy (ART) to HIV-negative controls. Methods A cross-sectional study including: 151 HIV-infected, ART-naive, 150 HIV-infected on ART and 153 HIV-negative adults. Traditional cardiovascular risk factors were determined by standard investigations. The primary outcome was ACC/AHA ASCVD Risk Estimator lifetime CVD risk score. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
7
19
0
Order By: Relevance
“…Thirty-two per cent of our study participants qualify for statin therapy under current ACC/AHA guidelines but only 2% were currently on statins. Juxtaposing our findings with those of a similar study from Tanzania24 shows an almost twofold higher statin requirement for our Indian HIV-infected population. While the proportion of participants that qualify for statins prescription decreases to 11% when using the NICE guidelines, our findings still highlight the deficit in therapeutic preventive services and a need to integrate them with the national HIV response.…”
Section: Discussionsupporting
confidence: 81%
“…Thirty-two per cent of our study participants qualify for statin therapy under current ACC/AHA guidelines but only 2% were currently on statins. Juxtaposing our findings with those of a similar study from Tanzania24 shows an almost twofold higher statin requirement for our Indian HIV-infected population. While the proportion of participants that qualify for statins prescription decreases to 11% when using the NICE guidelines, our findings still highlight the deficit in therapeutic preventive services and a need to integrate them with the national HIV response.…”
Section: Discussionsupporting
confidence: 81%
“…Among patients who were screened for all CVDRFs, 31% (53/172) were diagnosed with at least two CVDRFs, with the most common dyad of risks being HTN with either HC or DM (18% and 3%, respectively). CVDRF clustering in HIV‐infected individuals on ART has been previously observed in other resource‐limited settings and has been suggested to increase with duration on ART . Analysis of clustering patterns has been suggested as a method for differentiation and adjustment for true CVD risk in HIV‐infected patients …”
Section: Discussionmentioning
confidence: 74%
“…31 Analysis of clustering patterns has been suggested as a method for differentiation and adjustment for true CVD risk in HIV-infected patients. 5,51 A limitation of our study was the lack of an available control group because routine CVDRF screening was implemented only for HIV-infected patients. A second limitation is the lack of CVDRF screening at time of ART initiation.…”
Section: Discussionmentioning
confidence: 99%
“…When a total of 1,682 people who had no HIV at baseline were followed for about 80 months [ 35 ], BZD use was significantly associated with an increased rate of HIV seroconversion (adjusted risk ratio, 1.50; 95% CI, 1.01 to 2.24). A cross-sectional study enrolling a total 354 subjects [ 36 ] showed that cardiovascular disease occurrence was higher in HIV-infected patients than HIV-negative subjects. Another virus which can connect use of hypnotics and the risk of heart disease can be hepatitis C virus (HCV).…”
Section: Discussionmentioning
confidence: 99%